Does Caregiving Influence Planning for Future Aging?: A Mixed Methods Study Among Caregivers in Canada. (June 2021) - Gorenko, Julie A.; Konnert, Candace; Speirs, Calandra
A mixed method design was used to examine how caregiving and transitioning a family member into long-term care (LTC) influence planning. Participants, aged 50+ from the community, completed self-report questionnaires. Quantitative data evaluated differences between three groups (non-caregivers, caregivers, caregivers with experience in assisting with a LTC transition); and predictive effects of caregiving, care expectations and social support to planning. Interviews among a subsample of caregivers examined how experiences of caregiving, including assisting in a transition to LTC, and social support influenced planning. Results indicated that: (1) caregivers with LTC transition experience planned significantly more than non-caregivers, (2) caregiving, care expectations, and social support significantly predicted of planning, and (3) future care expectation was an important mechanism in the relationship between caregiving and planning. These findings underscore the impact of caregiving experiences on expectations of future care needs and preparation for future care needs, and the importance of social support.